Monetary Value Assessment of Clam Fishing Management Practices in the Venice Lagoon: Results from a Stated Choice Exercise - Paulo A.L.D. Nunes; Luca Rossetto; Arianne de Blaeij (Fondazione Eni Enrico Mattei (FEEM), 2003)
This article focuses on the economic valuation of alternative clam management practices in the Venice Lagoon. The proposed valuation method is characterized by the design of a survey questionnaire next to the fishermen population. In each questionnaire two fishing alternatives are described. The respondent is asked to choose one of them. This valuation method, referred in the article as conjoint valuation, gives sufficient flexibility to set, alter, and combine different management practices. Furthermore, this approach presents an important advantage to the well-known contingent valuation method since it makes the monetary valuation of each management attribute possible. Estimation results of the random utility model show that fishermen's willingness to pay for a larger clam fishing area is approximately 568 exteuro per year. In addition, an individual fisherman would be willing to pay 1,005 exteuro for a change from today's fishing situation practice towards a fishing practice exclusively based on vibrant rake system. If we take into account the interaction between fishing management attributes and fishermen characteristics, we can see that the valuation of each management practice differs substantially across the two populations. We can observe that the population of fishermen that operate in the cooperative regime presents not only a higher monetary valuation for an increase in the dimension of the fishing concession, which is now valued at 811 exteuro, but also a stronger willingness to pay for a change from today's fishing situation towards a fishing practice exclusively based on vibrant rake system, which is now estimated at 2,456 exteuro. Finally, the adoption of a clam fish management practice in Venice Lagoon that is exclusively based on the use of manual rakes, which is associated to the lowest damage to the Lagoon ecosystem, will represent a welfare loss of 5,904 exteuro per fisherman per year. Combining this value with the total number of fishermen currently operating in the Lagoon of Venice, the welfare loss associated with the adoption of such clam management policy that is exclusively based on the use of manual rakes amounts to 11.8 exteuro million per year. This figure can be regarded as an upper bound to the cost of implementation of a clam fishing system anchored in the use of manual, ecosystem friendly rakes.
Keywords: C25; C29; D62; H41; Q20; Q25; Q30; 330; Exotic marine species; Fishing rakes; Manila clam; Fishing effort; Open access; Welfare damages; Policy guidance; Permit price